Relationship between stock return and financial ratios: evidence from Malaysia - Ang, Hui Mei (2015)
This paper examines the explanatory power of dividend yield, earnings yield and bookto- market ratio towards future stock return in Malaysia. Panel Regression Analysis was performed to determine the relationship while diagnostic checks and robustness checks were executed to ensure the regression results are free from any econometric biases. The results of this study show that book-to-market ratio can be used to explain future stocks returns in full sample period, pre-crisis, during crisis and post crisis whereas dividend yield portray weak explanatory power in pre-crisis only. Since both dividend yield and book-to-market ratio can be used to predict future stock return, therefore it has contradicted with semi-strong form of market efficiency. Hence, it is believed that there is a possibility for investors to outperform the market.